THE CRISIS OF NATIONALISM IN INDONESIA-MALAYSIA BODER: A DISCOURSE ANALYSIS OF THE NARRATIVE FILM OF 'TANAH SURGA...KATANYA’ - I Nyoman Suaka; I Gede Bagus Wisnu Bayu Temaja (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aimed to identify the nationalism values in “Tanah Surga...Katanya” film. It is a qualitative descriptive study based on audiovisual of film. The results indicate that, in the border, the value of Indonesian nationalism is faded, such as lack of recognition of the Indonesia Rupiah, low appreciation on the national anthem, and looking down on the potential of the region. That condition is due to the government’s lack of attention to education, health, transportation, communication, and economic facilities. But, on the other hand, the spirit of nationalism and nationality emerged, as well as sacrifice to defend the country.